Implementasi Peraturan Gubernur tentang Tambahan Penghasilan Pegawai pada Badan Kepegawaian Daerah Provinsi Papua Barat - Saifullah, Aeb; Darmanto; Hafel, Muhlis (Syntax Literate, 2025)
This study is entitled Implementation of the Governor's Regulation on Additional Employee Income on the Regional Personnel Agency of West Papua Province. This research is motivated by the author's interest in the Implementation of West Papua Governor Regulation Number 19 of 2023 concerning Additional Employee Income for State Civil Apparatus within the West Papua Provincial Government, which regulation was issued with the background of providing additional employee income aimed at improving employee performance, but there are still some employees who have not been able to achieve this goal. In this study, the author uses the George C. Edward III model theory consisting of communication, policy resources, disposition or attitude of implementers, and bureaucratic structure. The method used in this study is a qualitative research method with data collection techniques carried out by collecting primary and secondary data through interviews and observations, for secondary data obtained from official documents, in the form of activity reports and applicable laws and regulations. The results of the study indicate that the Implementation of the Policy on Providing Additional Income for Employees at the Regional Personnel Agency of West Papua Province is not yet optimal, the regulations that have been set are still new so that many employees do not understand, there still needs to be intensive socialization so that the policies that will be implemented can be understood by all employees.